Non-Conventional and Sustainable Retrofitting of Fire-Exposed Reinforced Concrete Columns Using Basalt Fiber–Engineered Geopolymer Composites - Ruba Palanivelu; Bhuvaneshwari Panchanatham; Adamantis G. Zapris; Violetta K. Kytinou (Buildings)
The increasing demand for sustainable and resilient construction solutions calls for the integration of innovative, non-conventional materials in structural retrofitting. This study investigates the use of basalt fiber-based engineered geopolymer composites (BFEGC) as a retrofitting material for fire-damaged reinforced concrete (RC) short columns. A total of 14 columns (150 mm × 150 mm × 650 mm) were cast. Two columns were used as control specimens. The remaining 12 columns were exposed to various fire conditions: 300 °C for 30 min, 600 °C for 20 min, and 900 °C for 15 min, followed by gradual (GC) or rapid cooling (RC). Among the columns, six were left unwrapped (GC-NW, RC-NW), while six others were retrofitted with BFEGC (GC-W, RC-W) and subjected to axial loading until failure. The results showed that BFEGC wrapping improved the mechanical performance of fire-damaged columns, especially at 600 °C. The 600RC-W columns exhibited 1.85 times higher ultimate load, 1.56 times greater displacement ductility, and 2.99 times higher energy ductility compared to unwrapped columns. The strength index and confinement coefficient of the 600RC-W columns increased by 2.31 times and 40.2%, respectively. Microstructural analysis confirmed the formation of salient hydration products under elevated temperatures. BFEGC shows significant reduction in carbon emissions and embodied energy, compared to conventional cement-based binders for fiber-reinforced polymer systems.